Dating and Premarital Sexual Inisiation on Adolescence in Indonesia (KEMAS: Jurnal Kesehatan Masyarakat, 2019)
Adolescent is the generation that will determine the future of the nation. Indonesia has many adolescents with excellent achievement in national and international level. However, there are still many adolescents who have negative and deviant behavior such as smoking, drinking, using drugs, even to the behavior of free sex. The purpose of this analysis was to examine dating and sexual behavior of adolescents in Indonesia. This analysis was using secondary data from the Survey of Performance Indicators of National Medium Term Development Plan Program of the National Population and Family Planning Year 2015. The survey was conducted in 34 provinces throughout Indonesia. The number of the samples for this analysis were 41.885, who were adolescents aged 15-24 years and have not married yet. The analysis showed that male respondents who had girlfriend were higher than girls who had boyfriends. On average, the first dating age is 15.5 years. The most frequent activities during dating are holding hands, kissing lips, touching and stimulating the sensitive part of body. Boys were more permissive related premarital sex than adolescent girls. Furthermore, boys admitted have had sexual intercourse three times higher than girls. Adolescents who were on dating had higher chances of having premarital sex than those who were not on dating. The chance of premarital sex was likely to increase if the adolescents holding hands, kissing lips, and touching sensitive parts of body while having date.